Siklisasi Sitronelal Menggunakan Polimer Penyangga Katalis H2SO4 Berbahan Dasar Eugenol: Citronellal Cyclization Using Polymer Based-Eugenol Supported H2SO4 Catalyst - Moh. Rifki Saputra; Erwin Abdul Rahim; Husain Sosidi; Ni Ketut Sumarni (KOVALEN: Jurnal Riset Kimia, 2021)
Research on citronellal cyclization using a polymer based on eugenol supported H2SO4 catalyst has been carried out. The study aim was to determine the ratio of the addition of polymer based-eugenol supported H2SO4 catalyst used to produce the highest isopulegol. Citronellal cyclization was carried out using variations of catalyst concentration (1, 2, 3, 4, and 5%) and reaction time (30, 60, and 90 minutes). The results have obtained a yield of 50.67% found in the catalyst concentration of 1% and 90 minutes reflux time. From the results of GC-MS analysis, 29 compounds were read and among them isopulegol which was read at retention time 19.703 at peak 9 and peak area 4.76%. And the isopulegol results obtained are 11.34%.